Efficacy of Lecaniodiscus cupanioide and Alchornea cordifolia supplemented diets on neurotransmitter, neuroinflammatory, and antioxidant systems of scopolamine-induced amnesia in rat hippocampus - Odunayo Michael Agunloye; Ayodele Ebenezer Aijo; Olamide Wilson Fasakin; Ganiyu Oboh (Exploration of Neuroscience)
Aim: Natural products possess diverse pharmacological properties that are effective and safe for treating and managing amnesia; however, there is little or no scientific proof for most of their claims. This study evaluates the efficacy of Lecaniodiscus cupanioide-supplemented diets (LCSD) and Alchornea cordifolia-supplemented diets (ACSD) on scopolamine-induced amnesia in male rats. Roots of L. cupanioide and A. cordifolia were obtained and used to formulate 10% and 20% supplemented diets. Methods: Experimental animals were orally pre-fed LCSD and ACSD for 14 days before the induction of amnesia via single i.p. (intraperitoneal) administration of scopolamine (2 mg/kg body weight). Experimental animals were subjected to a Y-maze test to evaluate cognitive performance before experiment termination. The activities of hippocampal key enzymes linked to cognitive function were determined. Results: The result of the Y-maze showed that the induction of amnesia significantly (p < 0.001) reduced spatial memory function, which was protected against LCSD and ACSD pre-treated rats. Also, pre-treatment with supplemented diets inhibited the significant (p < 0.01) aggravation of monoamine oxidase, arginase, tumor necrosis factor-α, malonaldehyde, myeloperoxidase, acetylcholinesterase, and butyrylcholinesterase concentrations, and the significant (p < 0.05) depletion of dopamine, nitric oxide, interleukin-6, total thiol, and non-protein thiol concentrations, in comparison with that observed with amnesic-induced untreated rats. Comparatively, LCSD was more effective in preventing neuronal enzymatic imbalances, while ACSD was more effective in avoiding antioxidant status depletion. Conclusions: Conclusively, this study established that the supplemented diets possess potent anti-amnesic and neuroprotective abilities. Furthermore, this study recommends supplemented diets as a dietary intervention for preventing and managing amnesic conditions.